2018
DOI: 10.1016/j.schres.2018.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Expressed emotion as a predictor of the first psychotic episode — Results of the European prediction of psychosis study

Abstract: CHR subjects who perceive the most important person in their individual social environment to be limited in their stress coping skills had a higher risk of conversion to the first psychotic episode. The importance of this risk factor was further demonstrated by an improvement of risk estimation in the original EPOS predictor model. Perceiving a reference person as stress-prone and thus potentially unreliable might amplify self-experienced uncertainty and anxiety, which are often associated with the prodromal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 59 publications
3
24
0
Order By: Relevance
“…Despite global concerted efforts to improve the image of patients with MDs, stigma, negative attitudes, social exclusion, being dangerous to society, and discrimination contingent on multiple factors still persist against mentally ill population around the world and our study supported this notion [38][39][40][41][42][43]. Unlike family therapy and family and socio-religious supports that mediate protective role [44][45][46], unhealthy family interactions embedded in unhealthy criticisms, over-involvement and hostile attitude towards mentally ill patients tend to worsen their condition, cause relapse, acute psychotic decompensation, rehospitalization and poor outcome [47,48] that partly substantiated by the present online survey.…”
Section: Discussionsupporting
confidence: 68%
“…Despite global concerted efforts to improve the image of patients with MDs, stigma, negative attitudes, social exclusion, being dangerous to society, and discrimination contingent on multiple factors still persist against mentally ill population around the world and our study supported this notion [38][39][40][41][42][43]. Unlike family therapy and family and socio-religious supports that mediate protective role [44][45][46], unhealthy family interactions embedded in unhealthy criticisms, over-involvement and hostile attitude towards mentally ill patients tend to worsen their condition, cause relapse, acute psychotic decompensation, rehospitalization and poor outcome [47,48] that partly substantiated by the present online survey.…”
Section: Discussionsupporting
confidence: 68%
“…Although over the last 50 years most studies on EE have involved patients with schizophrenia, recent research has focused on the study of EE in relation to schizotypy [8], and the early course of psychosis [9,10]. Preliminary studies indicate that high-EE is already present in over half of the relatives of persons with first-episode psychosis (FEP) [11,12], and is even present in relatives of at-risk mental state (ARMS) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Small sample size is a major issue and only two studies measured EE at follow-up. The EPOS model suggests perceived irritability of a key relative to be most important and the key predictor of conversion for ARMS to FEP, whereas neither criticism nor EOI were significant predictors (Haidl et al, 2018). In comparison to the other studies included in this review, only patients" experiences were measured, which may suggest a biased perception.…”
Section: Limitations and Future Researchmentioning
confidence: 87%
“…The majority of caregivers were identified as first degree relatives, typically the mother. Haidl et al (2018) found mothers were chosen as the most influential person by a higher but non-significant proportion of individuals who transitioned to psychosis. Two studies (Tsai et al, 2015;McFarlane and Cook, 2007) examined differences in EE between mothers and fathers.…”
Section: Limitations and Future Researchmentioning
confidence: 98%
See 1 more Smart Citation